Renormalization of Generalized Quantum Electrodynamics - Bufalo, R. [UNESP]; Pimentel, B. M.; Zambrano, G. E.R. (Elsevier, 2015)
In the present work we shall study the renormalizability of Generalized Quantum Electrodynamics (GQED4). The on-shell renormalization scheme is reviewed and applied to the theory and we calculate the explicit expressions for all the counter-terms of the GQED4.
Keywords: Counter terms; Higher order derivative theory; Quantum field theory; Renormalization